Sudden death in epilepsy and ectopic neurohypophysis in Joubert syndrome 23 diagnosed using SNVs/indels and structural variants pipelines on WGS data: a case report - Sumathipala, Dulika (BMC Med Genet, 2020)
BACKGROUND: Joubert syndrome (JBTS) is a genetically heterogeneous group of neurodevelopmental syndromes caused by primary cilia dysfunction. Usually the neurological presentation starts with abnormal neonatal breathing followed by muscular hypotonia, psychomotor delay, and cerebellar ataxia. Cerebral MRI shows mid- and hindbrain anomalies including the molar tooth sign. We report a male patient with atypical presentation of Joubert syndrome type 23, thus expanding the phenotype. CASE PRESENTATION: Clinical features were consistent with JBTS already from infancy, yet the syndrome was not suspected before cerebral MRI later in childhood showed the characteristic molar tooth sign and ectopic neurohypophysis. From age 11 years seizures developed and after few years became increasingly difficult to treat, also related to inadequate compliance to therapy. He died at 23 years of sudden unexpected death in epilepsy (SUDEP). The genetic diagnosis remained elusive for many years, despite extensive genetic testing. We reached the genetic diagnosis by performing whole genome sequencing of the family trio and analyzing the data with the combination of one analysis pipeline for single nucleotide variants (SNVs)/indels and one for structural variants (SVs). This lead to the identification of the most common variant detected in patients with JBTS23 (OMIM# 616490), rs534542684, in compound heterozygosity with a 8.3 kb deletion in KIAA0586, not previously reported. CONCLUSIONS: We describe for the first time ectopic neurohypophysis and SUDEP in JBTS23, expanding the phenotype of this condition and raising the attention on the possible severity of the epilepsy in this disease. We also highlight the diagnostic power of WGS, which efficiently detects SNVs/indels and in addition allows the identification of SVs.